Mechanical fuel load reduction in Australia: a potential tool for bushfire mitigation. Issue 2 (3rd April 2017) - Ximenes, F.; Stephens, M.; Brown, M.; Law, B.; Mylek, M.; Schirmer, J.; Sullivan, A.; McGuffog, T.
ABSTRACT: Australia is the most fire-prone of all continents, with large areas of the country affected by bushfires each year. Bushfires can have profound impacts on communities and on the environment. Traditionally, prescribed burns have been used as a fuel reduction treatment. However, the proportion of land that is subjected to prescribed burns in Australia has decreased since 1990. This is partly due to the increasingly smaller windows of opportunity available to conduct burns safely, concerns about operational costs, health impacts from smoke, and the social acceptability of prescribed burning. These issues suggest a need for considering alternative fuel reduction approaches in select urban and rural areas, such as the potential for mechanical fuel load reduction (MFLR) treatments. The aim of MFLR is to reduce size, likelihood and severity of bushfires. In this paper we outline key considerations associated with the implementation of MFLR trials in Australia. We discuss issues such as assessing the effectiveness of MFLR in reducing fire risk, biomass change, potential harvest systems, cost-benefit analysis, social considerations and potential impacts on biodiversity. We conclude the paper with some discussion on policy considerations around the MFLR trials.